ABRUPT INCREASE IN PRECIPITATION AND WEATHERING OF SOILS IN EAST SIBERIA COINCIDENT WITH THE END OF THE LAST GLACIATION (15 CAL KYR BP) - Chebykin E.P.; Edgington D.N.; Grachev M.A.; Zheleznyakova T.O.; Vorobyova S.S.; Kulikova N.S.; Azarova I.N.; Khlystov O.M.; Goldberg E.L. (My University, 2002)
An abrupt increase in the temperature in Greenland in the wake of the initiation of the Bølling–Allerød warm phase at ca. 15 cal kyr BP was followed after a few decades by a dramatic increase in the concentration of methane in the atmosphere of the Earth resulting from an increase in humidity in the tropics [J.P. Severinghaus, E.J. Brook, Science 286 (1999) 930–934]. Analysis of a sediment core from Lake Baikal (East Siberia), spanning the end of the last glacial period and the Holocene, revealed an abrupt, stepwise, 1.3–3.4-fold decrease in the concentration of several ‘soluble’ elements such as Na, K, Mg, Ca and Si in hot nitric acid extracts of small intervals (3 cm). This chemical change appears to have occurred over the same time span, based on similarities in the profiles of silica and diatoms found in other 14C-dated cores. This suggests that the calcium-rich ‘mammoth steppe’ landscape [R.D. Guthrie, Quat. Sci. Rev. 20 (2001) 549–573] of Siberia created during the last glaciation underwent a dramatic transformation at the end of this period (at the beginning of the Bølling–Allerød warm phase) due to an increase in precipitation within a time interval of less than 300 yr.